Development of E-Modules Based on 5E Instructional Models in Chemistry - Siti Rahma; Z. Mawardi Effendi; Zuwirna; Indrati Kusumaningrum; Fetri Yeni J. (Postgraduate, University of Mataram, 2023)
Information technology in education opens up new opportunities to enhance learning in schools. The learning media that can be used is e-module, which is an interactive and flexible digital learning resource. This study aimed to develop an e-module based on the 5E instructional model in class XI chemistry at SMA. The development method used is 4D. Identify the needs and objectives of class XI chemistry learning. Furthermore, the structure and content of the e-module is prepared based on the 5E instructional model, namely: engage, explore, explain, elaborate, and evaluate. At the development stage, the e-module is designed and developed by taking into account the principles of instructional design that are in accordance with the characteristics of learning chemistry. E-modules are also equipped with multimedia, interactive simulations, practice questions, and automatic assessments to facilitate interactive learning. After the e-module has been developed, the implementation phase is carried out by testing the e-module in a sample group of class XI students in a high school. Furthermore, an evaluation of the effectiveness of the e-module was carried out through collecting data from students and teachers regarding the use, use, and satisfaction of the e-module. The results of this study are expected to improve the quality of high school chemistry learning, helping students be more active, creative, and independent in understanding complex chemical concepts. With the use of this e-module, learning is expected to be more interesting, interactive, and effective in achieving learning objectives